Properties of Accounting Income in Indonesia: Net Income and Total Comprehensive Income - Fitri Puspa, Dwi; Srimulatsih, Listiana; ., Zaitul (International Journal of Engineering and Technology, 2018)
Introduction- This study aims to investigate the quality of net income and total comprehensive earnings from four properties or characteristics. The characteristics in question are persistence, variability, predictability and value relevance. The samples of the research are manufacturing companies listed in Indonesian Stock Exchange in 2012. By employing sampling technique based on the criteria, 24 companies were selected as samples with period of data collection from2012 to 2014. There are six hypotheses tested by using regression technique. The results of the research show some findings, namely that net income is more persistent than total comprehensive income, there is no significant difference in the variability between total comprehensive income and net income, net income has the ability to predict cash flow and net income for the upcoming year is better than the total comprehensive income and the relevance of net income is different from the total comprehensive income both by applying price and return model. IFRS convergence financial accounting standards require companies that have public accountability in Indonesia to present a comprehensive income statement that includes the presentation of net income, other comprehensive income and total comprehensive income. The results of the research on the characteristics of net income and total comprehensiveness benefit for various parties such as investors, financial analysts and creditors concerned with the quality of profit that is characterized from 4 perspectives mentioned before.. For the financial accounting standards setter, results of this study provide information about the quality of comprehensive earnings.Â